Retinal Microvascular Abnormalities in Neurofibromatosis Type 1 Associated with Congenital Retinal Macrovessels - Shinji Makino; Katsuhisa Endoh; Hironobu Tampo (Case Reports in Ophthalmological Medicine)
Here, we report a case of retinal microvascular abnormalities in a patient with neurofibromatosis type 1 (NF1) associated with congenital retinal macrovessels. An abnormal retinal macrovessel, crossing the macula horizontally, was detected in the right eye. Additionally, retinal microvascular abnormalities were detected. Eight years after the initial visit, the retinal microvascular abnormalities were noted to have changed substantially. We speculate that retinal microvascular abnormalities in NF1 may change dynamically over the years.